Pragmatic Analysis of Illocutionary Acts of The Main Characters In It Ends with Us Movie - Naila Oxandiya Deselva (Fakultas Ilmu Budaya, 2025)
This research investigates the illocutionary acts performed by the main characters in It Ends with Us, a 2024 film adaptation of Colleen Hoover’s novel. The goal of this research is to examine the different kinds of illocutionary acts and their contextual factors. The researcher applied Searle’s (1979) and Halliday and Hassan’s (1989) theory to address the research problems. This study is a descriptive qualitative research whose data are not in the form of numbers but utterances. Data were collected from film subtitles with a focus on utterances categorized as indirect speech acts. The analysis results that directives have the highest frequency of occurrence (52.94%) with 9 utterances. It is followed by expressive, which has 4 utterances (23.53%), representatives, which has 3 utterances (17.65%), and commissives, which has only once utterance (5.88%). The declarative acts were not found in this movie. The dominance of directive and expressive speech acts shows that the characters in this film often convey commands, suggestions, or emotional responses indirectly. In addition, the analysis of the situational context helps to reveal the implied meanings in the speech that reflect themes such as emotional trauma, domestic violence, and forms of personal resistance. This study contributes to the study of pragmatics by showing that indirect illocutionary speech acts in film dialogue reflect complex interpersonal dynamics and how context shapes the intention and interpretation of communication.
Reupload file repository 5 Maret 2026_Ratna
Keywords: illocutionary acts; characters; implied meaning; movie